The compact genome of the plant pathogen Plasmodiophora brassicae is adapted to intracellular interactions with host Brassica spp. (December 2016) - Rolfe, Stephen; Strelkov, Stephen; Links, Matthew; Clarke, Wayne; Robinson, Stephen; Djavaheri, Mohammad; Malinowski, Robert; Haddadi, Parham; Kagale, Sateesh; Parkin, Isobel; Taheri, Ali; Borhan, M.
Abstract Background The protistPlasmodiophora brassicae is a soil-borne pathogen of cruciferous species and the causal agent of clubroot disease of Brassicas including agriculturally important crops such as canola/rapeseed (Brassica napus ).P. brassicae has remained an enigmatic plant pathogen and is a rare example of an obligate biotroph that resides entirely inside the host plant cell. The pathogen is the cause of severe yield losses and can render infested fields unsuitable for Brassica crop growth due to the persistence of resting spores in the soil for up to 20 years. Results To provide insight into the biology of the pathogen and its interaction with its primary hostB. napus, we produced a draft genome ofP. brassicae pathotypes 3 and 6 (Pb3 and Pb6) that differ in their host range. Pb3 is highly virulent onB. napus (but also infects other Brassica species) while Pb6 infects only vegetable Brassica crops. Both the Pb3 and Pb6 genomes are highly compact, each with a total size of 24.2 Mb, and contain less than 2 % repetitive DNA. Clustering of genome-wide single nucleotide polymorphisms (SNP) of Pb3, Pb6 and three additional re-sequenced pathotypes (Pb2, Pb5 and Pb8) shows a high degree of correlation of cluster grouping with host range. The Pb3 genome features significant reduction of intergenic space with multiple examples of overlapping untranslated regions (UTRs). Dependency on the host for essential nutrients is evident from the loss of genes for the biosynthesis of thiamine and some amino acids and the presence of a wide range of transport proteins, including some unique toP. brassicae . The annotated genes of Pb3 include those with a potential role in the regulation of the plant growth hormones cytokinin and auxin. The expression profile of Pb3 genes, including putative effectors, during infection and their potential role in manipulation of host defence is discussed. Conclusion TheP. brassicae genome sequence reveals a compact genome, a dependency of the pathogen on its host for some essential nutrients and a potential role in the regulation of host plant cytokinin and auxin. Genome annotation supported by RNA sequencing reveals significant reduction in intergenic space which, in addition to low repeat content, has likely contributed to theP. brassicae compact genome.